2007
DOI: 10.1038/sj.jes.7500571
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of regression models with land-use and emissions data to predict the spatial distribution of traffic-related air pollution in Rome

Abstract: Spatial modeling of traffic-related air pollution typically involves either regression modeling of land-use and traffic data or dispersion modeling of emissions data, but little is known to what extent land-use regression models might be improved by incorporating emissions data. The aim of this study was to develop a land-use regression model to predict nitrogen dioxide (NO 2 ) concentrations and compare its performance with a model including emissions data. The association between each land-use variable and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
2
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 38 publications
4
51
2
4
Order By: Relevance
“…Limited by data accessibility of traffic intensity, traffic counts and traffic emissions, which was also a problem in many other studies with the LUR model, we relied on road lengths and distance to the nearest road in this study. Previous studies have successfully applied the use of these two predictor variables, and some of them have reported that the performance of LUR models only using the lengths of roads were comparable with those using the traffic intensity or the traffic emission data for explaining the small-scale variability of pollutants concentrations (Henderson et al, 2007;Rosenlund et al, 2008). Population density is another predictor variable used frequently in LUR models for predicting NO 2 concentration.…”
Section: Discussionmentioning
confidence: 97%
“…Limited by data accessibility of traffic intensity, traffic counts and traffic emissions, which was also a problem in many other studies with the LUR model, we relied on road lengths and distance to the nearest road in this study. Previous studies have successfully applied the use of these two predictor variables, and some of them have reported that the performance of LUR models only using the lengths of roads were comparable with those using the traffic intensity or the traffic emission data for explaining the small-scale variability of pollutants concentrations (Henderson et al, 2007;Rosenlund et al, 2008). Population density is another predictor variable used frequently in LUR models for predicting NO 2 concentration.…”
Section: Discussionmentioning
confidence: 97%
“…The NO 2 concentration in the census block of residence (a small area of about 500 inhabitants per census block) was estimated for each child by a land use regression model described in detail elsewhere 24. This model was built by assessing the association between variables describing land use and traffic information and NO 2 concentrations measured at 68 sites in Rome.…”
Section: Methodsmentioning
confidence: 99%
“…Degradation of urban air quality attracted attention because of its adverse effects on human health (Makri and Stilianakis 2008;O'Connor et al 2008;Bernstein et al 2008;Kampa and Castanas 2008;Brunekreef 2007), its impact on material (Lorenzo et al 2007;Vallet et al 2006) and on visibility (Rokjin et al 2006;Young et al 2006;Hand et al 2002). Pollutant emissions, particularly from combustion for space heating and transportation (Braniš et al 2009;Tsikardani et al 2006;Bellander et al 2001;Rosenlund et al 2008;Costabile and Allegrini 2008;Yuval et al 2008;Fenger 1999), local meteorology (Fisher et al 2001(Fisher et al , 2006Aldrin and Haff 2005), and topography (Sládek et al 2007;Kadja et al 1998), are the main contributors to urban air pollution episodes.…”
Section: Introductionmentioning
confidence: 98%